1‐Phenyl‐1, 2, 4, 6‐cycloheptatetraene: the missing intermediate of the diphenylcarbene to fluorene rearrangement1. (9th October 2014) - Costa, Paolo; Sander, Wolfram; Moss, R. A.; Gudmundsdottir, A.
<x xml:space="preserve">Abstract</x> The photochemistry of diphenylcarbene 5, matrix‐isolated in argon at 3–5 K was investigated by UV–Vis, IR, and EPR spectroscopy. Although carbene 5 proved to be stable toward broadband UV irradiation, it slowly rearranges to 1‐phenyl‐1, 2, 4, 6‐cycloheptatetraene 8 during irradiation with the intense light of a 445‐nm diode laser. Other intermediates were not observed. Allene 8 is the key intermediate that was missing in the proposed mechanism of the rearrangement of 5 to fluorene 7. Copyright © 2014 John Wiley & Sons, Ltd.